Mechanical compression in cofacial porphyrin cyclophane pincers. Issue 27 (30th June 2022) - Hsu, Chunwei; Schosser, Werner M.; Zwick, Patrick; Dulić, Diana; Mayor, Marcel; Pauly, Fabian; van der Zant, Herre S. J.
Abstract : A two-order conductance increase upon stretching in porphyrin cyclophane pincer junctions is measured. Atomistic studies explain experimental observations by characteristic intramolecular changes in through-space and through-bond transport. Abstract : Intra- and intermolecular interactions are dominating chemical processes, and their concerted interplay enables complex nonequilibrium states like life. While the responsible basic forces are typically investigated spectroscopically, a conductance measurement to probe and control these interactions in a single molecule far out of equilibrium is reported here. Specifically, by separating macroscopic metal electrodes, two π-conjugated, bridge-connected porphyrin decks are peeled off on one side, but compressed on the other side due to the covalent mechanical fixation. We observe that the conductance response shows an exceptional exponential rise by two orders of magnitude in individual breaking events during the stretching. Theoretical studies atomistically explain the measured conductance behavior by a mechanically activated increase in through-bond transport and a simultaneous strengthening of through-space coupling. Our results not only reveal the various interacting intramolecular transport channels in a molecular set of levers, but also the molecules' potential to serve as molecular electro-mechanical sensors and switches.